2016
DOI: 10.1177/0003319716682120
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Visceral Adiposity Index and Homeostatic Model Assessment of Insulin Resistance in Participants With Normal Waist Circumference

Abstract: We assessed the correlation between the visceral adiposity index (VAI; a useful indicator of adipose distribution and function) and homeostatic model assessment of insulin resistance (HOMA-IR) in participants with normal waist circumference. A cross-sectional study was conducted, which included 1834 Chinese adults. The blood pressure, anthropometric measurements, fasting and postprandial blood glucose, fasting insulin, and lipid profiles were measured. The VAI and HOMA-IR were calculated. Participants were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 35 publications
(58 reference statements)
1
28
0
2
Order By: Relevance
“…The VAI was developed as an easy measurable indicator of visceral fat distribution and function . Subsequent studies confirmed its correlation with visceral fat distribution and insulin resistance, in addition also in patients with a normal WC and in those with polycystic ovary syndrome . In one of these studies, VAI showed an equally strong association with VAT accumulation as BMI and WC, while in another study both BMI and WC demonstrated a stronger relationship with VAT than VAI …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The VAI was developed as an easy measurable indicator of visceral fat distribution and function . Subsequent studies confirmed its correlation with visceral fat distribution and insulin resistance, in addition also in patients with a normal WC and in those with polycystic ovary syndrome . In one of these studies, VAI showed an equally strong association with VAT accumulation as BMI and WC, while in another study both BMI and WC demonstrated a stronger relationship with VAT than VAI …”
Section: Discussionmentioning
confidence: 94%
“…1 Subsequent studies confirmed its correlation with visceral fat distribution and insulin resistance, in addition also in patients with a normal WC and in those with polycystic ovary syndrome. [8][9][10][11][12][13] In one of these studies, VAI showed an equally strong association with VAT accumulation as BMI and WC, 8 while in another study both BMI and WC demonstrated a stronger relationship with VAT than VAI. 10 Associations between VAI and clinical or subclinical manifestations of cardiovascular disease (CVD) have been found in several studies.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies showed that VAI is a predictor of incident hypertension [9]. Ji et al reported that VAI has a strong correlation with insulin resistance even in a population without central obesity [10].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on the relationship between VAI and HOMA-IR, Randrianarisoa et al reported that VAI is positively associated with HOMA-IR in nondiabetic German (β = 0.42, p < 0.0001) [23]. Ji et al found that a very high VAI is the main risk factor for increased HOMA-IR in Chinese adults [24]. In the Framingham Heart Study, Preis et al reported that visceral adipose tissue and abdominal subcutaneous adipose tissue are positive correlates with insulin resistance and that visceral adipose tissue is a stronger correlate with insulin resistance than abdominal subcutaneous adipose tissue [25].…”
Section: Discussionmentioning
confidence: 98%